Iron and sulfur cycling in acid sulfate soil wetlands under dynamic redox conditions: A review. (April 2018) - Karimian, Niloofar; Johnston, Scott G.; Burton, Edward D.
Abstract: Acid sulfate soils (ASS) contain substantial quantities of iron sulfide minerals or the oxidation reaction products of these sulfidic minerals. Transformation of iron (Fe) and sulfur (S) bearing minerals is an important process in ASS wetlands with fluctuating redox conditions. A range of potentially toxic metals and metalloids can either be adsorbed on or incorporated into the structure of Fe and S bearing minerals. Therefore, transformation of these minerals as affected by dynamic redox conditions may regulate the mobility and bioavailability of associated metals/metalloids. Better understanding of the interaction between Fe/S biogeochemistry and trace metal/metalloid mobility under fluctuating redox conditions is important for assessing contaminant risk to the environment. This review paper provides an overview of current knowledge regarding cycling of Fe, S and selected trace metal/metalloids in ASS wetlands under fluctuating redox conditions and outlines future research challenges and directions on this subject. Graphical abstract: Image Highlights: Potential acid sulfate soils (PASS) contain substantial quantities of sulfidic minerals. Oxidation of sulfidic minerals in ASS environments generates acidity and secondary Fe(III) minerals. Seasonal redox oscillations can affect Fe and S speciation in ASS environments. Transformation of Fe and S mineral phases may regulate metalloids mobility in ASS environments. Dynamic redox can drive complex biogeochemical processes in freshwater re-flooded ASS.